Construction of Spiro[3-azabicyclo[3.1.0]hexanes] via 1,3-Dipolar Cycloaddition of 1,2-Diphenylcyclopropenes to Ninhydrin-Derived Azomethine Ylides - Wang, Siqi; Filatov, Alexander S.; Lozovskiy, Stanislav V.; Shmakov, Stanislav V.; Khoroshilova, Olesya V.; Larina, Anna G.; Selivanov, Stanislav I.; Boitsov, Vitali M.; Stepakov, Alexander V. (Synthesis, 2021)
The multi-component 1,3-dipolar cycloaddition of ninhydrin, α-amino acids (or peptides), and cyclopropenes for the synthesis of spirocyclic heterocycles containing both 3-azabicyclo[3.1.0]hexane and 2H-indene-1,3-dione motifs has been developed. This method provides easy access to 3-azabicyclo[3.1.0]hexane-2,2′-indenes with complete stereoselectivity and a high degree of atom economy under mild reaction conditions. A broad range of cyclopropenes and α-amino acids have been found to be compatible with the present protocol, which offers an opportunity to create a new library of biologically significant scaffold (3-azabicyclo[3.1.0]hexane). In addition, the сomprehensive study of mechanism of azomethine ylide formation from ninhydrin and sarcosine was performed by means of M11 density functional theory (DFT) calculations. It has been revealed that experimentally observed 1-methylspiro[aziridine-2,2′-indene]-1′,3′-dione is a kinetically controlled product of this reaction and appears to act as a 1,3-dipole precursor. This theoretical study also shed light on the main transformations of the azomethine ylide derived from ninhydrin and sarcosine such as a 1,3-dipolar cycloaddition to cyclopropene dipolarophiles, a dimerization reaction and a (1+5) electrocyclization reaction. The antitumor activity of some synthesized compounds against cervical carcinoma (HeLa) cell line was evaluated in vitro by MTS-assay.
Keywords: cyclopropenes; α-amino acids; peptides; stereoselectivity; reaction mechanism; DFT calculations; antitumor activity; cervical carcinoma (HeLa) cell line